Horacio y Sannazaro en las dos odas inéditas de Garcilaso de la Vega - Czepiel, M (Presses Universitaires de Bordeaux, 2023)
In this article I explore classical and contemporary literary influences, particularly those of Horace and Sannazaro, in the two recently discovered Latin odes of Garcilaso de la Vega. I study the theme of patronage in Ode IV, as well as analyzing the device of the recusatio and elements of the piscatorial eclogue in Ode V. I aim to demonstrate once again Garcilaso's transformative and eclectic practice of imitation in the Latin odes. El presente artículo analiza las influencias literarias clásicas y contemporáneas, en particular las de Horacio y Sannazaro, en las dos odas de Garcilaso de la Vega recién descubiertas. Se estudia el tema del patronazgo en la oda IV, y se analiza el tópico de la recusatio y los rasgos de la égloga piscatoria en la oda V, con el fin de ahondar en la estrategia de imitación de la poesía latina de Garcilaso.